Vegetative filters for improving environmental quality - Kalita, P.K.; Harner, Joseph P. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Nonpoint source pollution from agricultural areas has been recognized as a major contributor of surface and groundwater quality problems. Sediments, pesticide and nutrient runoffs, and microbial pathogens from farmlands may severely affect quality of water resources. A majority of Kansas river basins contains high concentrations of fecal coliforms, nitrogen, phosphorus, and sediments. The use of vegetative filters strips (VFS) has been identified as one of the best management practices to reduce pollutant concentrations in surface water sources. Vegetation planted between pollutant sources and receiving water accomplishes this by filtration, deposition, infiltration, adsorption, volatilization, plant uptake, and decomposition processes. The effectiveness of VFS in reducing nonpoint source pollution is being evaluated at four Kansas watersheds. Water samples are being collected at inlets and outlets of the VFS and analyzed for nutrients, sediments, and fecal coliform concentrations. Total nitrogen and phosphorus concentrations were reduced 26 and 14%, respectively, in one watershed and by 73 and 71%, respectively, in another. On a mass basis, total nitrogen and phosphorus reductions were 51 and 42%, respectively, in one and 60 and 52%, respectively, in the other. In the third watershed, mass flow rate of fecal coliform was reduced significantly by the VFS. If maintained properly, VFS can be used to improve water quality in agricultural areas.
Keywords: Beef; Environment; Feedlot; Nutrients; Vegetation